Various Risk Factors of Severe Acute Malnutrition in Children Under 5 Years of Age Presenting at a Secondary Care Hospital - Shahzad Ahmed, Nazimuddin, Shazia Mahar, Zamir Ahmed Qambrani, Abdul Hameed Radhan, Col (R) Imran Ahmed, Muhammad Nadeem Chohan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the various risk factors of severe acute malnutrition in children under 5 years of age presenting at a secondary care hospital Study design: A cross-sectional study Place and duration: Nutritional stabilization centre, Pediatric department, civil hospital Mirpur Khas from January to June 2022 Methodology: A total of 321 children (both males and females) below the age of 5 years were enrolled in this study. Severe acute malnutrition was diagnosed on the basis of weight for height/length Z score criteria. (ie < - 3 SD). Children were managed at a nutritional stabilization centre according to WHO management criteria. History was taken regarding breastfeeding, age of complementary feeding, immunization, maternal education level and repeated diarrhea. Counts with percentages were reported on age group, sex, mother education, lack of breastfeeding, delayed weaning, lack of immunization, and diarrhea. Association was tested with sex and mother education status using the Pearson Chi-Square test. P-values less than 0.05 were considered statistically significant. The bar chart also reported the study outcomes with gender. Results: In the present study, there were three hundred twenty children with mean age 17.9 of (SD=±10.3) months, 30.6% were aged 9 – 12 months, 55.9% were male gender, and 65.6% of mothers were uneducated. Lack of breastfeeding was observed in 10.3% of children, delayed weaning was 12.5%, lack of immunization was 14.1%, and diarrhea was found in 20.6% of children. Children with uneducated mothers 11% were found to have a lack of breastfeeding, 84.2% with delayed complementary feeding, 81% with a lack of immunization and 26.2% with diarrhea. Conclusion: According to our study lack of breast feeding, delayed weaning, lack of immunization, recurrent diarrhea and maternal education are strongly associated with severe acute malnutrition in children. Uneducated women breastfeed their children more, but they start complementary feeding late and their children are more unvaccinated and had more frequent diarrhea which leads to severe acute malnutrition. Keywords: severe acute malnutrition, breastfeeding, diarrhea, complementary feeding